Trocas simbólicas entre gerações: avós, netos e a literatura infantil - Silva, Camila Cuencas Funari Mendes e; Correa, Mariele Rodrigues [UNESP] (My University, 2014)
This work aims at understanding the intergenerational relationships between grandparents and grandchildren in contemporary society. To this end, we analyze two works of Children's Literature as a form of manifestation of the importance of symbolic exchanges between generations. Selected Menina Nina: duas razões para não chorar, Ziraldo (2002) and A menina, o cofrinho e a vovó by Cora Coralina (2009). We adopt a psychoanalytic reading as a reference for analysis, since it excels in psychic construction of the individual, his unconscious design and its interaction with the socio-cultural environment , which allows to explore and reflect on the links between generations , thus serving as a research method and interpretation of relationships within the family . We confirm our hypothesis with writers - grandparents, here represented by Ziraldo and Cora Coralina, which produced works that highlight the experience with their grandchildren. Thus, grandparents, grandchildren and readers are active in recovery and symbolic transmission characters.

Este trabalho tem como objetivo a compreensão das relações intergeracionais entre avós e netos na sociedade contemporânea. Para tanto, analisamos duas obras da Literatura Infantil como uma das formas de manifestação da importância das trocas simbólicas entre gerações. Selecionamos Menina Nina: duas razões para não chorar, de Ziraldo (2002) e A menina, o cofrinho e a vovó, de Cora Coralina (2009). Adotamos a leitura psicanalítica como referencial para análise, uma vez que ela prima pela construção psíquica do indivíduo, sua concepção inconsciente e sua interação com o meio sociocultural, o que possibilita explorar e refletir sobre os vínculos entre gerações, servindo assim, como método de pesquisa e interpretação das relações no contexto familiar. Confirmamos nossa hipótese com os escritores-avós, aqui representados por Ziraldo e Cora Coralina, que produziram obras que enaltecem a experiência com seus netos. Desse modo, avós, netos e leitores são personagens ativos na valorização e transmissão simbólicas.
Symbolic exchanges between generations: grandparents, grandchildren and children's literature
Keywords: Grandparents and grandchildren; Intergenerational relationships; Family; Children's literature; Avós e netos; Relações intergeracionais; Família; Literatura infantil